Diagnostic imaging in the management of older adults with low back pain: analysis from the BAck Complaints in Elders: Chiropractic – Australia cohort study - Hazel J. Jenkins; Kristin Grace; Anika Young; Felix Parker; Jan Hartvigsen; Sidney M. Rubinstein; Simon D. French; Katie de Luca (Chiropractic & Manual Therapies)
Abstract Background Diagnostic imaging is commonly used in the management of low back pain (LBP), with approximately one-quarter of those who present to primary care referred for imaging. Current estimates of imaging frequency commonly exclude older adults; however, pathology detected with imaging (e.g., osteoporosis, cancer) may occur more frequently in older populations. The aims of this study were to: (i) determine the frequency and forms of diagnostic imaging use in older adults presenting for chiropractic care for LBP in Australia; (ii) describe participant characteristics associated with imaging use; and (iii) describe the types of radiographic findings. Methods Data were collected from the BAck Complaints in Elders: Chiropractic-Australia (BACE: C-A) study, a 12-month, prospective cohort study of adults aged ≥ 55 years with a new episode of LBP. Self-reported frequency of imaging use (baseline, 2 and 6 weeks, 3, 6, 9, and 12 months) was reported descriptively by imaging modality. Imaging reports were obtained, and imaging findings were independently extracted and categorised. Baseline characteristics were assessed for differences in those who received imaging compared to those who did not. Proportions of imaging use and imaging findings were presented descriptively with 95% confidence intervals. Results The BACE: C-A cohort comprised 217 participants of whom 60.8% reported receiving diagnostic imaging for their current episode of LBP. X-ray was performed most (44.7%), followed by computed tomography (CT) (30.8%). Participants receiving imaging reported higher low back disability, more healthcare use for LBP, more frequent leg pain, more suspected serious pathology, and stronger beliefs that imaging was important. Degenerative changes were the most common imaging finding (96.6%). Pathology of possible clinical significance, including compression fracture or suspected osteoporosis, was present in 15.5% of participants. Conclusion Three out of five older adults with LBP who sought chiropractic care received imaging over one-year. Participants receiving imaging tended to have more complex presentations (e.g., more disability, suspected underlying pathology) or stronger beliefs that imaging was necessary for the management of LBP. Degenerative changes were the most common imaging finding. Pathology of potential clinical relevance was present on approximately 15% of imaging reports received. No conditions requiring immediate medical attention were reported.